Salivary Factors that Maintain the Normal Oral Commensal Microflora. (June 2020) - Carpenter, G.H.
The oral microbiome is one of the most stable ecosystems in the body and yet the reasons for this are still unclear. As well as being stable, it is also highly diverse which can be ascribed to the variety of niches available in the mouth. Previous studies have focused on the microflora in disease—either caries or periodontitis—and only recently have they considered factors that maintain the normal microflora. This has led to the perception that the microflora proliferate in nutrient-rich periods during oral processing of foods and drinks and starves in between times. In this review, evidence is presented which shows that the normal flora are maintained on a diet of salivary factors including urea, lactate, and salivary protein degradation. These factors are actively secreted by salivary glands which suggests these factors are important in maintaining normal commensals in the mouth. In addition, the immobilization of SIgA in the mucosal pellicle indicates a mechanism to retain certain bacteria that does not rely on the bacterial-centric mechanisms such as adhesins. By examining the salivary metabolome, it is clear that protein degradation is a key nutrient and the availability of free amino acids increases resistance to environmental stresses.